Cardiopulmonary alterations by ultrasound in a patient with uncomplicated mixed malaria infection: a case report from the Amazon Basin - Alma Wegener (Malaria Journal, 2021)
Abstract Background Information on cardiopulmonary complications in clinical malaria is sparse and diagnosis may be difficult in resource-limited areas due to lack of proper diagnostic tools and access to medical care. A case of pericardial effusion and pulmonary alterations assessed by ultrasound in a patient with uncomplicated mixed malaria infection is described. Case presentation A previously healthy 23-year-old male from the Amazon Basin was diagnosed with mixed infection of Plasmodium vivax and Plasmodium falciparum by peripheral blood smear. The patient presented with mild malaria symptoms without signs of severe malaria, but reported moderate chest pain and shortness of breath. Laboratory analyses revealed thrombocytopenia and anemia. The electrocardiogram had PR depressions and bedside ultrasound of the cardiopulmonary system showed pericardial effusion (18 mm) accompanied by multiple B-lines in the lungs, identified as vertical artifacts extending from the pleural line. Cardiac biomarkers were normal. The patient was treated according to national guidelines for malaria and suspected pericarditis, respectively. At follow-up on day 5, the pericardial effusion (9mm) and B-lines had markedly decreased. By day 21 the patient was asymptomatic, had completed the treatment, and the electrocardiogram and ultrasound findings had normalized. Conclusions This case report highlight the usefulness of bedside ultrasound to identify cardiopulmonary involvement in patients with uncomplicated malaria and relevant symptoms.